The influence of stand age on benthic decomposition and recycling of organic matter in managed mangrove forests of Malaysia - Alongi, D.M.; Sasekumar, A.; Tirendi, F.; Dixon, P. (Elsevier, 1998)
Decomposition of sediment organic matter was examined in relation to forest age in 2-, 15- and 60-year old, managed Rhizophora apiculata (Blume) stands in the Matang Mangrove Forest Reserve of peninsular Malaysia. Rates of O2 consumption (range: 11.5–21.4 mmol m−2 d−1) and CO2 production (range: 8.9–20.9 mmol m−2 d−1) were equivalent among the forests indicating that early diagenesis is not linked to stand age and age-related differences in rates of forest production. There were, however, site differences in the dominance of specific diagenetic pathways. Rates of sulfate reduction (to 40 cm depth) averaged 8.9±3.1 mmol S m−2 d−1 and 7.2±0.3 mmol S m−2 d−1 in the 15- and 60-year old forests, respectively, accounting for most (75–125%) of the total mineralization. In contrast, sulfate reduction (3.0±0.5 mmol S m−2 d−1) constituted a considerably smaller proportion (42%) of total organic matter oxidation at the 2-year old forest. Rates of solute efflux across the sediment-water interface and vertical profiles of dissolved Mn and NO2−+NO3− suggest that manganese reduction and denitrification–nitrification, coupled with aerobic respiration, account for most oxidation of organic matter at the 2-year old forest. The loss of particulate organic matter and the increased importance of aerobic and suboxic processes in the 2 year-old forest suggest some impact from disturbance of tree removal. A shift to proportionally less sulfate reduction in sediments of regenerating forests may result in greater availability of dissolved nutrients and some trace metals, and serve to reduce exposure of R. apiculata seedlings to anoxic, toxic solutes (e.g., sulfides). This diagenetic shift may facilitate rapid seedling growth and regeneration of forests.